Directions for food security auditing - Kovalenko S. N.; Sivkova A. E.; Semenova N. A.; Kovalenko Y. N. (BIO Web of Conferences)
Background. This study examines the process of food security auditing as a comprehensive assessment of the system ensuring food supply to the population. Objective. The research aims to outline key directions for food security auditing and develop indicators for quantifying the level of food security. Materials and methods. The research predetermines the study of the regulatory framework, as well as a review of the opinions of various authors on the problems of food security in Russia. The methodological basis of the study were the methods of analysis, induction, deduction, abstraction in the context of the selected topic. Results. The study explores critical aspects such as risk identification, food quality and accessibility assessment, and resource management, considering environmental, economic, and social factors. Special attention is given to the stages of preparation, data collection, analysis, and the development of recommendations to enhance the resilience of the food system. The research underscores the importance of integrating international standards and employing advanced analytical methodologies, such as HACCP, to achieve high levels of food safety and quality. The article also presents key quantitative indicators for food security assessment and offers practical recommendations for mitigating risks associated with food shortages or quality deterioration. Conclusion. The study concludes that a systematic approach to food security auditing necessitates the integration of environmental, economic, and social considerations.